Remote ischemic conditioning in ST-elevation myocardial infarction as adjuvant to primary angioplasty (RIC-STEMI): study protocol for a randomized controlled trial. Issue 1 (December 2015) - Gaspar, António; Pereira, Miguel; Azevedo, Pedro; Lourenço, André; Marques, Jorge; Leite-Moreira, Adelino
Abstract Background ST-elevation myocardial infarction (STEMI) accounts for nearly one third of acute coronary syndromes. Despite improved STEMI patient care, mortality remains high, contributing significantly to the ischemic heart disease burden. This may partly be related to ischemia-reperfusion injury (IRI). Remote ischemic conditioning (RIC), through short cycles of ischemia-reperfusion applied to a limb, has been shown to reduce IRI in various clinical settings. Our primary hypothesis is that RIC will reduce adverse events related to STEMI when applied as adjunctive therapy to primary percutaneous coronary intervention (PCI). Methods/Design "Remote ischemic conditioning in ST-elevation myocardial infarction as adjuvant to primary angioplasty" (RIC-STEMI) is an ongoing prospective, single-center, open-label, randomized controlled trial to assess whether RIC as an adjunctive therapy during primary PCI in patients presenting with STEMI can improve clinical outcomes. After enrollment, participants are randomized according to a computer-generated randomization schedule, in a ratio of 1:1 to RIC or no intervention, in blocks of four individuals. RIC is begun at least 10 min before the estimated time of the first balloon inflation and its duration is 30 min. Ischemia is induced by three cycles of inflation of a blood pressure cuff placed on the left lower limb to 200 mmHg and then deflation to 0 mmHg for another 5 min. Primary endpoint is a combined endpoint of death from cardiac cause or hospitalization for heart failure (HF) on follow-up (including device implantation: implantable cardioverter defibrillator, cardiac resynchronization and left ventricular assist device). Secondary endpoints are myocardial infarction (MI) size (estimated by the 48 h area under the curve of serum troponin I levels), development of Q-wave MI, left ventricular function (assessed by echocardiography within the first 3 days after admission), contrast-induced nephropathy, in-hospital mortality, all-cause mortality and, finally, major adverse cardiovascular events. Patients will have a minimum follow-up period of 12 months. From 11 March 2013 to 31 December 2014, 324 patients have been enrolled and randomized. We expect to complete enrollment of the 494 patients deemed necessary within 3 years. Trial registration ClinicalTrials.gov identifier:NCT02313961 ; registered on 8 December 2014.